Phytochrome B and the Regulation of Circadian Ethylene Production in Sorghum - Finlayson, Scott A. (American Society of Plant Physiologists, 1998)
The sorghum (Sorghum bicolor L. Moench) cultivar 58M, which contains the null mutant phytochrome B gene, shows reduced photoperiodic sensitivity and exhibits a shade-avoidance phenotype. Ethylene production by seedlings of wild-type and phytochrome B mutant cultivars was monitored every 3 h, and both cultivars were found to produce ethylene in a circadian rhythm, with peak production occurring during the day. The phytochrome B mutant produces rhythmic peaks of ethylene with approximately 10 times the amplitude of the wild-type counterpart with the same period and diurnal timing. The source of the mutant's additional ethylene is the shoot. The diurnal rhythm can be produced with either light or temperature cycles; however, both light and temperature cycles are required for circadian entrainment. The temperature signal overrides the light signal in the production of diurnal rhythms, because seedlings grown under thermoperiods reversed with the photoperiod produced ethylene peaks during the warm nights. To examine the effect of extreme shading on ethylene production, seedlings were grown under dim, far-red-enriched light. This treatment duplicated the phytochrome B mutant's shade-avoidance phenotype in the wild type and caused the wild type to produce ethylene peaks similar to those observed in the mutant. The results confirm that phytochrome B is not required for proper function of circadian timing, but it may be involved in modulating physiological rhythms driven by the biological clock oscillator.